Indirect associations of pain resilience and kinesiophobia with the relationship between physical activity and chronic pain - Niederstrasser, Nils Georg; Attridge, Nina; Slepian, P. Maxwell (PLOS ONE, 2025)
Background Pain is associated with a decrease in physical activity for most individuals. Nevertheless, some individuals manage to maintain physical activity levels despite pain. While the exact psychological mechanisms behind this are unknown, it may possibly be due to low kinesiophobia and high pain resilience levels. This study aimed to examine the direct and indirect associations of pain resilience and kinesiophobia with the relationship between pain and physical activity. Methods In this cross-sectional study data were collected from 172 participants suffering from chronic pain. Three path models were fitted to assess the indirect associations between pain resilience and kinesiophobia in the relationship between physical activity and musculoskeletal pain individually and simultaneously. Additionally, a linear regression model was fitted to examine the impact of psychological predictors of physical activity while accounting for musculoskeletal pain. Results Significant proportions of the association between musculoskeletal pain on physical activity occurred through both pain resilience and kinesiophobia. Nevertheless, when examined simultaneously, only the indirect associations via pain resilience remained significant. Similarly, when predicting physical activity levels, only high levels of pain resilience and male gender were associated with increased physical activity levels, whereas kinesiophobia was not. Conclusions This highlights the central role pain resilience plays in retaining physical activity levels when faced with chronic pain. It also implies that pain resilience predicts physical activity levels beyond pain intensity, kinesiophobia, pain duration, and pain spread. It is, therefore, imperative to examine avenues of increasing pain resilience among individuals suffering from chronic pain, not only to improve their pain, but also their overall health and well-being. This possibly bears implications for clinical practice and may inform treatment approaches, whereby pain resilience may be boosted to increase physical activity levels. Nevertheless, given the cross-sectional design, longitudinal and experimental studies are needed to confirm the causal pathways.